Psicología ascética y psicología epistémica (2006)
ABSTRACT: Two tendencies have been present in psychology since antiquity to our days: the ascetic tendency (purifi cation, self care and transformation of the soul) and the epistemic tendency (systematic knowledge of the soul). Both of them are evidence of the undeniable philosophical foundation of psychology. With modern science and its Galilean paradigm, some thinkers believed that it was possible to leave behind the philosophical past and turn psychology into a natural science. This paper emphasizes that philosophical inheritance is essential for psychology and points out that not all the schools in that discipline intend to become a science. Finally, the paper shows that ascetic and epistemic tendencies can be dialectically articulated in psychology.